Are Disability Images in Advertising Becoming Bold And Daring? An Analysis of Prominent Themes in US and UK Campaigns - Haller, Beth A.; Ralph, Sue (Disability Studies Quarterly, 2006)
Advertisements featuring disabled people have become more noticeable in the United States (USA) and Great Britain/United Kingdom (UK) in the last decade. The focus of this article is to qualitatively analyze a selection of these advertisements since 1999 to understand how disability currently is being used within advertising messages. The goal of the analyses are to understand whether advertising images remained static in their messages or are expanding their messages to show a variety of disability images. The findings revealed that some improvements have occurred in advertising images of disability, such as the themes of empowerment (Cingular) and the themes of disability pride and inclusion (Doritos, Marks & Spencer, and HSBC). However, several ads still embrace antiquated themes that continue to stigmatize disabled people, such as the Nuveen, HealthExtras, and Bank of America ads. These themes convey underlying messages that disabled people are broken and in need of repair, are awash in tragedy, or are Supercrips, who are put on pedestals for just living their lives.